English Learning Community in English Village dan Meningkatkan Berkomunikasi Kelas 5(A) MI Al-Hidayah - makhrus ali khotami; M. Bambang Edi Siswanto (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Language is a bridge to the world and education is one form of initial capital in learning so that students are able and can understand the importance of changes in learning that are applied to students with the progress of globalization and the language used using English because this international language that I apply at MI Al-hidayah and learning models that are fun and students are easy to understand gem and song learning models that apply songs and games so that elementary school children are more happy in learning because students do not feel learning but they get maximum results can communicate and students can memorize vocabulary prose words English is easy and easy, we as researchers are looking for an easy method and in learning so that students can learn without any pressure. Here students learn English, there is no coercion and they enjoy this method with pronunciation and practice in class and students. a is invited to play gems and enjoy the learning. The problems studied in this study are about how the phenomena of student learning take shape, how to cultivate student discipline and how appropriate methods in democratic learning can foster student learning discipline at MI Al-hidayah. student learning, describe how to foster curiosity and increase student learning. This research uses a qualitative research approach with descriptive qualitative research. The subjects of this study were students, education staff and language village students. This research was conducted from February 2022 to June 2022. The data collection methods used were observation, interviews and documentation methods. The validity of the data was obtained by source triangulation method.